2018
DOI: 10.22261/jgpps.i9ab30
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between total pressure losses of highly loaded annular diffusers and integral stage design parameters

Abstract: Diffusers convert kinetic flow energy into a rise in static pressure. This pressure recovery is the primary aerodynamic design objective for exhaust gas diffusers in power-generating steam and gas turbines. The total pressure loss is an equally important diffuser design parameter. It is strongly linked to the pressure recovery and the residual kinetic energy of the diffuser outlet flow. A reduction benefits the overall thermodynamic cycle, which requires the adjacent components of a diffuser to be included in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 16 publications
(26 reference statements)
0
5
0
Order By: Relevance
“…The influence of the dynamic pressure on wake mixing is characterised by II,r l . Details on the definition of Λ can be found in [14]. It was demonstrated that the rectified total pressure loss coefficient correlates well with Σ for numerical and experimental data, as seen in Fig.…”
Section: Total Pressure Lossesmentioning
confidence: 68%
See 3 more Smart Citations
“…The influence of the dynamic pressure on wake mixing is characterised by II,r l . Details on the definition of Λ can be found in [14]. It was demonstrated that the rectified total pressure loss coefficient correlates well with Σ for numerical and experimental data, as seen in Fig.…”
Section: Total Pressure Lossesmentioning
confidence: 68%
“…The ratio r l incorporates a simple Fig. 2 Absolute difference in rectified diffuser total pressure loss from reference Δ against stabilisation number Σ (adapted from [14]) estimate for the velocity deficit. The influence of the dynamic pressure on wake mixing is characterised by II,r l .…”
Section: Total Pressure Lossesmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite their greatly simplified geometries, their correlations still provide valuable predictions and the TCFs of many modern aero engine architectures cluster in a parametric region, which was identified as optimal by their work (Göttlich 2011;Gräsel et al 2006). Notwithstanding, other less crucial geometrical parameters still influence the performance of TCFs (Gräsel et al 2006;Wallin and Eriksson 2008;Mimic et al 2018).…”
Section: Introductionmentioning
confidence: 99%